1989
DOI: 10.1037/0022-0663.81.3.347
|View full text |Cite
|
Sign up to set email alerts
|

Schemata training and transfer of an intellectual skill.

Abstract: Advice and feedback pertaining to analogical reasoning were manipulated to produce varying practice conditions for college-age Ss. Following training, Ss were administered a transfer task that was used to identify the transfer of a general or a specific procedural strategy for solving verbal analogies. Both a general transfer effect for verbal analogy solution and a procedural transfer effect for cause-effect relationships were obtained. These transfer effects were observed for both immediate and delayed trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
45
1
2

Year Published

1992
1992
2004
2004

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 14 publications
6
45
1
2
Order By: Relevance
“…It was observed that both groups of subjects were able to retrieve deep principles from the available visual sources, and create successful analogies. These findings contrast with Gick and Holyoak (1980), Novick (1988), and Phye (1989) who claimed that novices often have difficulties to spontaneously access, and use relevant analogies. We propose that instructions to use analogy, together with the large collection of within-and between-domain visual displays made available to subjects played a role in this.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…It was observed that both groups of subjects were able to retrieve deep principles from the available visual sources, and create successful analogies. These findings contrast with Gick and Holyoak (1980), Novick (1988), and Phye (1989) who claimed that novices often have difficulties to spontaneously access, and use relevant analogies. We propose that instructions to use analogy, together with the large collection of within-and between-domain visual displays made available to subjects played a role in this.…”
Section: Discussioncontrasting
confidence: 75%
“…Experience in a certain domain allows the generation of abstract problem representations, and enhances the probability of structural mappings from source to target. Difficulties in the spontaneous access and use of analogy were reported to be associated with the level of expertise in several studies (Gick and Holyoak 1980;Needham and Begg 1981;Phye 1989). Accordingly, novices often fail to recognize how new problems can be viewed in terms of old problems, and are believed to lack sufficient skills to benefit from explicit instructions to use analogy.…”
Section: Experts and Novices: The Use Of Analogymentioning
confidence: 99%
“…Aggregates of traces acting in concert at the time of retrieval represent the category as a whole (Hintzman, 1986). Schema abstraction in a multiple-trace memory model would account for the on-line transfer of procedural and strategic knowledge (Phye, 1989) during acquisition as well as results obtained with memory-based processing (Phye, 1990(Phye, , 1991. The schema-abstraction model reflects the relative emphasis placed on decision making at the time of retrieval in contrast to an emphasis during encoding.…”
Section: Learning and Memorymentioning
confidence: 99%
“…Alternatively, domains can be defined in terms of the formal nature of processing or procedures required (Kolers and Roediger, 1984;Klauer, 1990;Phye, 1989Phye, , 1990). Sternberg's (1985) generativity principle has been employed (Phye, 1991;Phye and Sanders, 1992a,b) to define problem domains based on the type of strategy processing required for problem solution.…”
Section: The Right Tools For the Jobmentioning
confidence: 99%
See 1 more Smart Citation